2020
DOI: 10.1155/2020/5649165
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on Hypertension and Self-Care Practice among Adult Hypertensive Patients at University of Gondar Comprehensive Specialized Hospital, Ethiopia, 2019

Abstract: Background. Patients with hypertension need to be aware of various aspects of hypertension and exercise self-care. But, there is limited information regarding this issue. Objective of the Study. This study was designed to assess knowledge on hypertension and self-care practice among adult hypertensive patients in the University of Gondar Comprehensive Specialized Hospital, Ethiopia. Materials and Methods. Descriptive cross-sectional study was conducted among 384 hypertensive patients from April to May 2019. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 23 publications
3
28
3
2
Order By: Relevance
“…In this subgroup analysis, more than three-fourth (77%, 95% CI 69% to 85%) of the hypertensive patients were following the recommended alcohol consumption. This finding is similar to that of the study conducted in Nepal (84%) 44 and Iran (86.7%), 41 42 but higher than that of a study conducted in Kenya (49.5%). 31 39…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this subgroup analysis, more than three-fourth (77%, 95% CI 69% to 85%) of the hypertensive patients were following the recommended alcohol consumption. This finding is similar to that of the study conducted in Nepal (84%) 44 and Iran (86.7%), 41 42 but higher than that of a study conducted in Kenya (49.5%). 31 39…”
Section: Discussionsupporting
confidence: 87%
“… 41 43 Our finding was lower than that of the study conducted in Nepal (80%). 44 In the opposite side, our finding was lower than that of the study conducted in Iran (100%). 41 42 …”
Section: Discussioncontrasting
confidence: 78%
“…Despite widespread prevalence of hypertension, and its prediction to rise steeply, 22 previous and current studies have shown that low patient awareness about the hypertension, its risks, and complications is ubiquitous. Many studies [23][24][25] report that the patients have poor to average knowledge regarding hypertension, despite of the range of sources of information available. Common factors impacting knowledge uptake with regards to Pakistan may be illiteracy and poverty.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Thailand among hypertensive patients in Bangkok showed that although hypertensive patients were aware of their uncontrolled hypertension, they still chose to have a high salt diet due to a preference for tastier and instant food [48]. The pattern of the findings from other countries was similarly observed, such as in Ethiopia [49,50], Nepal [42], India [51,52], Australia [53], Iran [54,55], Spain [56], and Korea [57]. These studies revealed that individuals generally have a reasonable knowledge of the salt and its adverse effects of overconsumption as well as their favorable attitudes toward salt reduction; however, almost none of them took action to reduce salt intake, and their blood pressure was still uncontrolled.…”
Section: Discussionmentioning
confidence: 85%